ANALISIS BIBLIOMETRIK DALAM IMPLEMENTASI PROJECT BASED LEARNING DALAM MEMBANGUN KETERAMPILAN BERPIKIR KREATIF - Lestari, Eunike Dwi; Atmojo, Idam Ragil Widianto; Daryanto, Joko (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This study aims to analyze the development of the implementation of Project based learning (PjBL) in building creative thinking skills through bibliometric analysis methods. The analysis focuses on three main aspects: (1) publication trends and identification of the most productive authors, (2) collaboration patterns between authors, institutions and countries, and (3) research topic trends based on keyword co-occurrence analysis. The study uses a bibliometric approach by analyzing 466 articles from the Scopus database for the 2014-2024 period. The data was analyzed using VOSviewer software for bibliometric network visualization and Mendeley for reference management. The results of the study revealed three main findings: First, there was a significant increase in the number of publications with the dominance of contributions from Indonesia (95 publications) and the United States (80 publications), with the State University of Malang as the most productive institution. Second, the collaboration pattern shows the formation of three implementation models: regional collaboration (especially in Southeast Asia), international (Asia-America-Europe), and interdisciplinary. Third, the keyword co-occurrence analysis reveals the evolution of the research focus from the development of the basic framework (2014-2016), to the integration of technology (2016-2018), to the holistic implementation with an emphasis on soft skills and psychological aspects of learning (2018-2020). These findings provide an empirical basis for the development of more effective PjBL implementation in building creative thinking skills.